2002
DOI: 10.1073/pnas.222657499
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced muscle fat oxidation and glucose transport by ACRP30 globular domain: Acetyl–CoA carboxylase inhibition and AMP-activated protein kinase activation

Abstract: gACRP30, the globular subunit of adipocyte complement-related protein of 30 kDa (ACRP30), improves insulin sensitivity and increases fatty acid oxidation. The mechanism by which gACRP30 exerts these effects is unknown. Here, we examined if gACRP30 activates AMP-activated protein kinase (AMPK), an enzyme that has been shown to increase muscle fatty acid oxidation and insulin sensitivity. Incubation of rat extensor digitorum longus (EDL), a predominantly fast twitch muscle, with gACRP30 (2.5 g͞ml) for 30 min led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
601
3
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 885 publications
(655 citation statements)
references
References 44 publications
30
601
3
21
Order By: Relevance
“…We subsequently investigated the effects of gAd on glucose uptake and metabolism in these cells. Consistent with previous observations in rat skeletal muscle and C 2 C 12 myocytes [6,10,11], gAd increased glucose uptake in L6 myotubes. Importantly, we have demonstrated that gAd increases glucose uptake by increasing the cell surface content of GLUT4myc.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We subsequently investigated the effects of gAd on glucose uptake and metabolism in these cells. Consistent with previous observations in rat skeletal muscle and C 2 C 12 myocytes [6,10,11], gAd increased glucose uptake in L6 myotubes. Importantly, we have demonstrated that gAd increases glucose uptake by increasing the cell surface content of GLUT4myc.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in line with our data indicating that gAd increases the transport V max for glucose without altering the K m . Previous studies have suggested that adiponectin regulates glucose uptake via an AMP kinase-dependent mechanism [6,10]. AMP kinase activation by AICAR has been shown to increase glucose uptake via [24,25], or independently of [26] GLUT translocation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations